KEBUTUHAN MATERI KULIAH BAHASA INDONESIA MAHASISWA JURUSAN NONBAHASA INDONESIA - Pranowo Pranowo (Universitas Negeri Yogyakarta, 2005)
Abstract This research was aimed at resolving two problems: (1)What Indonesian Language subject matters are appropriate for the students of non-Indonesian Language major? (2) What kind of instructional method is appropriate the students of non-Indonesian major? The subjects of this research are 100 students of non-Indonesian Language major, who have taken the Indonesian Language course at the Sanata Dharma University. The result of this research is as follows: (1)most of the 100 students have the opinion that the Indonesian Language course should be emphasized more on the lesson on writing scientific compositions, and (2)the instructional method used should give the students ample opportunity to conduct individual learning and to do exercise. Keywords: need assessment, Indonesian language course